Assessment of Sanitation Practices in Incremental Housing in Ilaro, Yewa South Local Government Area, Ogun State - Vincent Uwala; Kehinde Olabode E (Garuda Prestasi Nusantara Consulting, 2021)
Incremental housing process has become a major mode of housing production for low income groups in urban centres in most developing countries. Existing literature on incremental housing focused on incremental housing finance with little attention on sanitation practices of inhabitants of incremental housing. This study, therefore, examined current sanitation practices in incremental housing in Ilaro with a view to influencing policy direction in furtherance of an improved sanitation practice. The research adopted survey research and mixed method of sampling techniques involving purposive and systematic sampling techniques. Itolu community was purposely selected due to the preponderance of uncompleted occupied buildings in the area. Automated counting of digitized buildings in the study area resulted in 540 out of which 115 were found to be uncompleted inhabited through ground-truthing. Fifty (50%) of the one hundred and fifteen (115) identified uncompleted occupied buildings were sampled using systematic sampling techniques. The study revealed that majority of the sampled houses in the area lacks sanitation facilities. Similarly, it established an unsustainable method of waste disposal among the residents of the area. The study recommended that the provision of essential sanitation facilities should be a prerequisite for housing habitation in the country and enforcement of existing sanitation regulations.